Challenges and Enablers of Spiritual Care for Family Members of Patients in the Intensive Care Unit. (March 2020) - Roze des Ordons, Amanda L.; Stelfox, Henry T.; Grindrod-Millar, Kathleen; Sinuff, Tasnim; Smiechowski, Jennifer; Sinclair, Shane
Spiritual care has been recognized as important to family members of critically ill patients, although it is often not integrated within clinical practice. We conducted focus groups and interviews with family members, spiritual health practitioners, and clinicians who work in the intensive care unit (ICU) to explore their experiences of working with family members experiencing spiritual distress in this setting. Challenges and factors that enable identification and support for spiritual distress were identified, as well as suggestions for improvement.